ANALISIS KANDUNGAN ZAT PEMUTIH “KLORIN” PADA IKAN ASIN DI PASAR TRADISIONAL (PABEAN) SURABAYA TAHUN 2015 - Novi Alita Anuradha; AT. Diana Nerawati; Erna Triastuti (GEMA LINGKUNGAN KESEHATAN, 2015)
Salted fish which uses Non Food Additives are often found in the community. Chlorine bleachmaterial is feared to be added to the salted fish sold in traditional markets. Chlorine is an importantchemical in water purification, disinfectant, bleach, and mustard gas.This is a descriptive research with the objective of determining the chlorine contained in somekinds of salted fish sold in "Surabaya PabeanMarket" by conducting laboratory tests and physicalquality assessment, as well as sellers level of knowledge about food bleaching agents. The resultindicated that 23 samples contained chlorine and 7 samples of salted fish dis not containchlorine.Quantitative laboratory test  on salted fish samples showedthat out of 30 samples, allpositive contained chlorine (100%) with the highest level in medananchovies type of 9.335 ppmand the lowest was on the type of Gulama salted fish at 0.0103 (requirement of 0,00 or negative)that was banned to added to food by Permenkes 033 of 2012 on Food Additives. Measurementontraders’ level of knowledge on the production of salted fish shows that 9 out of 15sellerspossessed a good level of knowledge about the food bleach substance. To prevent salted fish containing chlorine, Department of Healthand other health institutions are suggested to conduct education to traders on the dangers of chlorine used in food by the that theydo not use chlorine as a bleaching agent.